Understanding greenspace attachment across the life-course: the role of personal history in establishing spatial meaning amongst older people in the Netherlands - Lauwerijssen, Rachel; Mell, Ian; Barker, Adam (Frontiers in Sustainable Cities, 2025)
IntroductionGreenspaces facilitate bonds between people and place and may hold meaning in improving health and wellbeing. Studies indicate that contact with nature can promote health, but the evidence relies on cross-sectional study designs and lacks studies incorporating a life-course perspective. Understanding greenspace attachment across a lifetime may hold meaning in improving lifelong health and wellbeing. It remains unclear how and why people, independent of their life-stage, develop and maintain an attachment to greenspace.MethodsThis exploratory study explores the role of personal experiences and memories in developing and nurturing greenspace attachment across a lifetime, focusing on older adults’ personal histories. Semi-structured, oral history focused interviews (n = 20) were conducted in 2019 with residents living in Breda and Tilburg (the Netherlands).ResultsThe findings suggest that significant personal experiences helped participants to form attachments to various types of greenspaces regardless of their life stage and greenspace typology. The childhood life phase is a crucial phase for participants to develop greenspace attachment and their attachment varies through their lifetime. Everyday greenery is perceived as an essential part to their local environment and assists in maintaining attachments and restoration.DiscussionUnderstanding the creation and fostering of greenspace attachment can inform urban planning initiatives, streetscape design, and greenspace management to prioritise the design and planning of multifunctional, intergenerational, and inclusive greenspaces that cater to the needs, interests, and values for people across all age groups.